The determination of the law applicable to the contract for the assignment of receivables with an international element. Regarding the judgment of the Provincial Court of Soria of June 21, 2022 - Sánchez Cano, Mª Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Disputes involving an assignment of receivables with an international element raise numerous problems, particularly as regards the area of applicable law. In the case of the judgment under consideration, the Provincial Court of Soria rejects the direct application of domestic private law, without prior recourse to the rules of private international law in force in Spain, declaring that the Court is empowered to apply ex officio the conflict rules relating to the law applicable to the contract of assignment of receivables. This, with the purpose of verifying whether the procedural succession by transfer of the disputed claim in favor of the plaintiff company has validly taken place.